2015
DOI: 10.1099/vir.0.000122
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 splicing is controlled by local RNA structure and binding of splicing regulatory proteins at the major 5′ splice site

Abstract: The 59 leader region of the human immunodeficiency virus 1 (HIV-1) RNA genome contains the major 59 splice site (ss) that is used in the production of the many spliced viral RNAs. This splice-donor (SD) region can fold into a stable stem-loop structure and the thermodynamic stability of this RNA hairpin influences splicing efficiency. In addition, splicing may be modulated by binding of splicing regulatory (SR) proteins, in particular SF2/ASF (SRSF1), SC35 (SRSF2), SRp40 (SRSF5) and SRp55 (SRSF6), to sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
0
24
1
Order By: Relevance
“…Our data suggest that the SLSA1 structure is important to A1 usage; other splice acceptors and splice control elements are also located in or near structural features, and many of these regions have been studied for their ability to bind cellular splice factors (49,50). It will be informative to continue to characterize the roles that these and other structures play in splicing regulation by creating mutations that alter either structure or cellular factor binding sites.…”
Section: Discussionmentioning
confidence: 87%
“…Our data suggest that the SLSA1 structure is important to A1 usage; other splice acceptors and splice control elements are also located in or near structural features, and many of these regions have been studied for their ability to bind cellular splice factors (49,50). It will be informative to continue to characterize the roles that these and other structures play in splicing regulation by creating mutations that alter either structure or cellular factor binding sites.…”
Section: Discussionmentioning
confidence: 87%
“…The virus has developed strategies to maintain transcript homeostasis by using cis RNA sequence elements that recruit host RNA-binding proteins to modulate the activities of donor and acceptor sites. The series of events that control HIV-1 splicing are not well understood; however, there is growing precedence that RNA structure modulates HIV-1 splicing (46,47). Therefore, an understanding of mechanisms that determine how frequently a splice site gets utilized requires accurate knowledge of the RNA interactions surrounding it.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of a large set of HIV-1 sequences revealed that all three regulatory features of the 59ss region are highly conserved in different group M viruses, which supports an important function during virus replication. Modulation of the splicing frequency reduces HIV-1 replication and, as previously discussed (Mueller et al, 2015), the HIV-1 splicing process is an interesting target for antiviral therapy. …”
mentioning
confidence: 99%
“…DNA affect splicing efficiency when tested in the context of a destabilized SD hairpin structure (Mueller et al, 2015). However, two putative SRSF2 sites [SRSF2 (1) and SRSF2 (2) ] are present upstream of the 59ss.…”
mentioning
confidence: 99%
See 1 more Smart Citation